Investigation of Antioxidant Activities of Melissa officinalis and Lavandula angustifolia Extracts against Chromium Induced Oxidative Damage in Saccharomyces cerevisiae with Molecular Biological and Biochemical Biomarkers - Beyaz, Seda (Mattioli 1885, 2022)
Background and aim: Melissa and Lavandula are known to exhibit high antioxidant and strong biological activities thanks to their rich polyphenol and aromatic content. In this study, eight groups were created to investigate whether Melissa and Lavandula have a protective role against chromium damage in Sac-charomyces cerevisiae (S. cerevisiae). Methods: Application groups: (i) Control Group; (ii) Chromium (30 mM); (iii) Melissa (20%); (iv) Lavandula (20%); (v) Melissa (20%) + Lavandula (20%); (vi) Melissa (20%) + Chro-mium (30 mM); (vii) Lavandula (20%) + Chromium (30 mM); (viii) Melissa (20%) + Lavandula (20%) + Chromium (30 mM). S. cerevisiae cultures were grown at 30 degrees C for 1, 3, 5 and 24 hours. Cell growth, malon-dialdehyde (MDA) analyzes, glutathione (GSH) levels, catalase (CAT) activities were determined by spec-trophotometer. Total protein concentrations were determined by sodium dodecyl sulphate polyacrylamide gel electrophoresis (SDS-PAGE) and bradford method. Results: According to the results, when compared with the chromium group, cell growth (1, 3, 5 and 24 hours), total protein synthesis, GSH level (24 hours) and CAT level (24 hours) increased in Melissa, Lavandula and Melissa + Lavandula while MDA level (24 hours) decreased. Melissa and Lavandula plant extracts, which are rich in polyphenolic compounds, were found to provide antioxidant protection and reduce oxidative damage in S. cerevisiae culture. Conclusions: Thus, it is thought that it will contribute to new treatment methodologies by providing effective protection in the treat-ment of many diseases thanks to its strong antioxidant and anti-inflammatory properties.
Keywords: electrophoresis; cell growth; oxidative damage; protein; Saccharomyces cerevisiae